Предмет: Математика,
автор: AnnaPoznikova
разложите на множители выражение: 6a^3c^2-15a^2c^3-9a^2c^4
Решите уравнение: (4x+1)*(2x-4)-8x^2=3*(6-x)
Ответы
Автор ответа:
0
1.
6a³c² - 15a²c³ - 9a²c^4 = 3а²с² * (2а - 5с - 3с² 0,
2.
(4x+1)*(2x-4) - 8x² = 3*(6-x),
8х² - 16х + 2х - 4 - 8х² - 18 + 3х = 0,
-11х - 22 = 0,
-11х = 22,
х = 22 : (-11),
х = -2
6a³c² - 15a²c³ - 9a²c^4 = 3а²с² * (2а - 5с - 3с² 0,
2.
(4x+1)*(2x-4) - 8x² = 3*(6-x),
8х² - 16х + 2х - 4 - 8х² - 18 + 3х = 0,
-11х - 22 = 0,
-11х = 22,
х = 22 : (-11),
х = -2
Похожие вопросы
Предмет: Қазақ тiлi,
автор: zulakendibaeva
Предмет: История,
автор: alyona2043
Предмет: Английский язык,
автор: 1234567dgj
Предмет: Литература,
автор: dapama070105
Предмет: История,
автор: Афанасьева1